Amphiphilic pentaazamacrocyclic manganese superoxide dismutase mimetics - Lieb, Dominik; Kenkel, Isabell; Miljkovic, Jan; Moldenhauer, Daniel; Weber, Nadine; Filipovic, Milos; Gröhn, Franziska; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2014)
Five newly functionalized pentaazamacrocyclic manganese complexes, with variable lengths and amounts of the aliphatic groups (three compounds with one linear chain containing 12, 16, and 22 carbon atoms, i.e., MnL1, MnL2, and MnL3, respectively, as well as two compounds containing two C12 and C16 chains, MnL4 and MnL5, respectively) that are derivatives of the known SOD mimetic, Mn(Me-Pyane), have been synthesized. These amphiphilic complexes were characterized by the ESI mass spectrometry, potentiometric titrations, light scattering, cyclic voltammetry, and direct stopped-flow determination of their SOD activity at pH 8.1 and 7.4 (in phosphate and HEPES buffers). The formation of supramolecular aggregates that predominantly exist in the solution as a defined micellar/nanostructure assembly, with an average 400 nm size, has been demonstrated for MnL1. The biological effects of the selected complexes (MnL1 and MnL2) on the superoxide level in cytosol and mitochondria have been tested, as well as their effects on the prevention of the lipid peroxidation induced by paraquat. Advantages and disadvantages of the lipophilic pentaazamacrocyclic manganese SOD mimetics in comparison to the corresponding nonsubstituted SOD active complex have been discussed. © 2013 American Chemical Society.

Light-Responsive Size of Self-Assembled Spiropyran-Lysozyme Nanoparticles with Enzymatic Function - Moldenhauer, Daniel; Fuenzalida Werner, Juan Pablo; Strassert, Cristian A.; Gröhn, Franziska (Biomacromolecules, 2019)
Novel light-responsive nanoassemblies with switchable size and enzymatic activity are built from a protein and a water-soluble spiropyran. Assemblies are created by electrostatic self-assembly in aqueous solution such that the photochromic property of the spiropyran enables light responsiveness. Upon visible light exposure, the aggregate size increases from 200 to 400 nm. The enzyme retains its activity upon aggregation into the assembly, while it decreases through visible light irradiation. Fundamentally, we show how the two different spiropyran isomers, the open-ring merocyanine form and the closed-ring spiropyran form, bind differently to the protein, which triggers the assembly size and use of thermodynamic data to understand the binding process and the size response. Thus, as a proof of concept, a self-assembly driven light-tunable enzyme activity in conjunction with a triggerable assembly size is demonstrated for a model system. The concept bears future potential for various possible biological applications ranging from genetic control over vaccine applications to the detection of certain proteins.
CRIS-Team WoS Importer:2019-03-06